Acne vulgaris - review on pathogenesis and treatment - Żmuda, Bartłomiej; Żuberek, Michał; Ślusarczyk, Daniel; Pisera, Piotr; Kiełkowicz, Aleksandra; Popińska, Zuzanna; Pactwa, Filip; Jakubowska, Wiktoria (Journal of Education, Health and Sport, 2024)
Introduction: Acne vulgaris is a common dermatological problem, resulting from a complex interaction of many factors. This article presents a comprehensive overview of the pathogenesis of this condition, examining key aspects such as inflammatory factors, sebum production, colonization by P. acnes, endocrine disruption and lifestyle influences. In addition, various treatments are discussed, including the effectiveness of isotretinoin-based therapy and the potential benefits of antibiotics and retinoids in specific patient groups. Aim of study: The aim of the study is to summarize the available knowledge about the Acne vulgaris. The epidemiology, etiology, and methods of treatment were summarized and described. Materials and methods: The literature available in PubMed database was reviewed using following keywords: “Acne vulgaris”, “Isotretinoin”, “Therapy of Acne”. Conclusion: Research into acne vulgaris has been extensive, yet variations in study methods and descriptions have prevented definitive conclusions. Tailored care for each patient is crucial due to these differences. The disease's development involves various factors including inflammatory mediators, excess sebum production, P. acnes colonization, hormonal imbalances, and lifestyle impacts. Isotretinoin remains the most effective treatment, albeit with potential side effects that need consideration. For specific patient groups, topical antibiotics and retinoids may offer beneficial effects.